Studies on pyrimidines: Part IV: Synthesis and Antibacterial Activity of 6-(2’ -Hydroxy-5’ -methylphen-1’ -yl)-3-p-acetanilide Sulphonyl-4-substitutedphenyl-3,4-dihydropyrimidine-2-thiols. - CHAMPANERI, H.R.; NAIK, H.B.; Modi, S.R. (Asian Journal of Chemistry, 2010)
The title compounds have been synthesised and screened for their antibacterial activity against S. aurcus and E. coli.